Diverging trends for acute lower respiratory infections in non-Aboriginal and Aboriginal children - Moore, H.; Burgner, D.; Carville, K.; Jacoby, P.; Richmond, P.; Lehmann, Deborah (Blackwell Scientific Publications, 2007)
IngentaConnect * Home * About Ingenta * Ingenta Labs * Ingenta Blog * Help o Check our FAQs o Or contact us to report problems with: o Subscription access o Article delivery o Registration o Library administrator tasks o Other problems * For Publishersdown arrow o Why go online? o Why choose IngentaConnect? o Beyond Print: enhancing your service o Access and authentication o Article purchasing o Managing your publications o Usage statistics o Reference linking services o Branding opportunities o Keeping in touch o Contact us * For Researchersdown arrow o For Authors o About IngentaConnect o Search and browse o Publications available o Accessing articles o Managing your account o Creating marked lists o Creating Saved searches o Receiving email alerts o Subscribing to RSS feeds o Software compatibility o Ingenta Labs o Register * For Librariansdown arrow o Resource Zone o Why choose IngentaConnect? o Why choose IngentaConnect Complete? o Activating Subscriptions o Document delivery o Linking to IngentaConnect o Alerting & RSS feeds o Other library services o Keeping in touch o Register logo Diverging trends for lower respiratory infections in non-Aboriginal and Aboriginal children Authors: Moore, Hannah; Burgner, David1; Carville, Kylie2; Jacoby, Peter2; Richmond, Peter1; Lehmann, Deborah2 Source: Journal of Paediatrics and Child Health, Volume 43, Number 6, June 2007 , pp. 451-457(7) Publisher: Blackwell Publishing * < previous article * | * next article > * | * view table of contents Key: Free Content - Free Content New Content - New Content Subscribed Content - Subscribed Content Free Trial Content - Free Trial Content Abstract: Aim: To investigate temporal trends in admission rates for acute lower respiratory infections (ALRI) in a total population birth cohort of non-Aboriginal and Aboriginal children. Methods: Retrospective analysis of linked population-based data using the Western Australian Data Linkage System. All singleton live births in Western Australia between 1990 and 2000 were included. Hospital admission rates per 1000 live births for ALRI before age 2?years and linear time trends for ALRI admission rates were investigated. Results: ALRI admission rates were 7.5 (95% confidence interval (CI) 7.2-7.7) times higher in Aboriginal than non-Aboriginal children (337 vs. 45 per 1000 live births); pneumonia rates were 13.5 (95% CI 12.8-14.4) times higher and bronchiolitis rates were 5.8 (95% CI 5.3-6.0) times higher. ALRI admission rates rose in non-Aboriginal children (<12?months, 6%/year, P?<?0.002; 12-23?months, 11%/year, P?<?0.001) but declined in Aboriginal children aged 12-23?months (4%/year, P?=?0.003). Bronchiolitis rates rose in all children, especially non-Aboriginal infants aged <12?months (13%/year, P?<?0.001), while pneumonia rates rose in non-Aboriginal children but declined in Aboriginal children. Declines in bronchitis and asthma were also noted. Conclusion: There has been an increase in incidence of bronchiolitis before age 12?months. For children aged 12-23?months a diagnostic shift from asthma and bronchitis to bronchiolitis and changes in health service utilisation are likely explanations for diverging temporal trends. The continuing disparity between Aboriginal and non-Aboriginal children needs to be addressed and appropriate preventative measures for ALRI, and in particular bronchiolitis, are urgently needed. Keywords: hospitalisation; Indigenous population; infant; respiratory infection; Western Australia Document Type: Research article DOI: 10.1111/j.1440-1754.2007.01110.x Affiliations: 1: School of Paediatrics and Child Health, University of Western Australia, Perth, Western Australia, Australia 2: Telethon Institute for Child Health Research, Centre for Child Health Research and The full text article is available for purchase $54.87 plus tax Credit/debit card Institutional payment account OR Purchase later * < previous article * | * next article > * | * view table of contents Back to top Key: Free Content - Free Content New Content - New Content Subscribed Content - Subscribed Content Free Trial Content - Free Trial Content * Website © 2008 Ingenta. Article copyright remains with the publisher, society or author(s) as specified within the article. * Terms and Conditions * Privacy Policy * Information for advertisers Page Help Click here for Page Help Browse Search Electronic content Fax/Ariel content Journal or book title Subscribed titles Advanced search * Search history Shopping cart Tools * Print * Article access options * Export options o EndNote o BibTEX * Linking options o IngentaConnect o OpenURL o DOI * Alerting options o Receive New Issue Alert o Latest TOC RSS Feed o Recent Issues RSS Feed * Bookmarking options o Marked List o Add to Marked List o Post to del.icio.us o Post to Furl o Post to CiteUlike o Post to Connotea o Post to Bibsonomy Signed in as: + The University of Western Australia-Library Additional sign in | Sign out Sign in User name Password Remember me * forgotten your password? * Sign in via Athens Need to register? Sign up here Text size: A | A | A | A